Etonogestrel implant failure in a woman taking thyroid hormone replacement: A case report - Alice Moylan; Jewel Brown; Melissa J. Chen; Mitchell D. Creinin (Case Reports in Women's Health)
The etonogestrel implant is known to have high contraceptive efficacy for up to 5 years. This case report describes etonogestrel implant failure during year 4 of use in a patient with a normal body mass index. The patient was receiving thyroid hormone replacement after a thyroidectomy and was found to have iatrogenic thyrotoxicosis in the months preceding pregnancy. Further study of the effects of thyroid hormone on etonogestrel metabolism are indicated.